Influence of the electrode/electrolyte interface structure on the performance of Pr0.8Sr0.2Fe0.7Ni0.3O3-δ as Solid Oxide Fuel Cell cathode. (10th May 2017) - Giuliano, Alice; Nicollet, Clément; Fourcade, Sébastien; Mauvy, Fabrice; Carpanese, Maria Paola; Grenier, Jean-Claude
Graphical abstract: Abstract: The effect of gadolinium-doped ceria (GDC) interlayer on the Pr0.8 Sr0.2 Fe0.7 Ni0.3 O3-δ (PSFN8273) cathode performance and stability in solid oxide fuel cell (SOFC) operating conditions is investigated. Two different symmetrical half-cells, with dense GDC electrolyte pellet (GDC/PSFN cell) and with GDC interlayer deposited on yttria stabilized zirconia pellet (YSZ) (YSZ/GDC/PSFN cell), are prepared and characterized by electrochemical impedance spectroscopy (EIS) as a function of temperature. The fitting of the data is carried out using an adapted Equivalent Circuit (EC). The polarization resistance ( Rp ) is higher for the YSZ/GDC/PSFN cell compared to GDC/PSFN cell. This increase is assigned to the interface microstructure. Then, the electrochemical properties of the half-cell with GDC interlayer are measured in three-electrode configuration under dc cathodic overpotential. In addition, the long-term stability is evaluated through an ageing test applying a current density of −123 mA.cm −2 for 1000 hours at 700 °C under air. PSFN8273 appears to be stable as cathode with a decrease in overpotential of about 6% in the first 200 hours and a subsequently stabilization. These results mean that even if the GDC interlayer affect the cathode performance (in terms of Rp ) it did not influence its stability, making PSFN8273 a suitable material as cathode for SOFC application.